Латинска соматска фразеологија: фраземи со компонента pectus во римскиот sermo amatorius - Кочовска, Светлана (Здружение за компаративна книжевност на Македонија (ЗККМ), Здружение на класични филолози „Антика“, 2016)
The aim of this paper is to give a brief overview of the Latin idioms with the lexeme pectus (‘a breast’) as a main component. The study is based on a corpus of Latin literary texts which share love as a theme. It includes the complete works of Plautus, Catullus, Tibullus, Propertius and Ovid. The study of the uses of the lexeme pectus in the selected corpus shows that the Romans conceptualized the breast as a seat of human intellectual capacities (pectus alicui sapit, sapеre aliquid pleno pectore, in pectore rem volutare, in pectore aliquid fovere, recoluere rem pectore etc.), as a seat of emotions and character traits (pectus alicui ardere, aliquis pectore uri, pectora trepidare/pavere [formidine/metu], pectus alicui peracescere, pectus alicui virere felle etc.) and as an equivalent to the notion of man (pectora nota, pectora fidissima, pectora selecta).
Somatic Phraseology in Latin: Idioms with the Lexeme Pectus in the Roman Sermo Amatorius
Keywords: латинска фразеологија, соматски фраземи, pectus